2021
DOI: 10.1186/s40163-021-00150-z
|View full text |Cite
|
Sign up to set email alerts
|

Using crime script analysis to elucidate the details of Amur tiger poaching in the Russian Far East

Abstract: Poaching is the most direct threat to the persistence of Amur tigers. However, little empirical evidence exists about the modus operandi of the offenders associated with this wildlife crime. Crime science can aid conservation efforts by identifying the patterns and opportunity structures that facilitate poaching. By employing semi-structured interviews and participants observation with those directly involved in the poaching and trafficking of Amur tigers in the Russian Far East (RFE), this article utilizes cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Tiger parts, such as skin, bones, claws, whiskers, canines, penises, and so on, are in demand in the market. Skidmore ( 2021 ), says that the demand for poached parts is different because people use different things for different purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Tiger parts, such as skin, bones, claws, whiskers, canines, penises, and so on, are in demand in the market. Skidmore ( 2021 ), says that the demand for poached parts is different because people use different things for different purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Its first application was manifested in the Lemieux and Clarke 2009 study of elephant poaching in Africa [ 25 ]. Subsequently, researchers have applied these theories to the study of parrot poaching in Latin America [ 26 , 27 ] and Indonesia [ 28 ]; illegal commercial fishing [ 29 , 30 ]; illegal recreational fishing [ 31 , 32 ]; tiger poaching [ 33 ]; human–leopard conflict [ 34 ]; redwood burl poaching [ 35 ]; and others. The collective findings of these studies have demonstrated the utility of examining such crimes through the environmental criminological theoretical lens, because evidence-based intervention strategies can then be directly derived from within these theoretical foundations to effectively deal with such problems.…”
Section: Methodsmentioning
confidence: 99%
“…It also must be acknowledged that in some cases, certain illegal wildlife trades boost local rural economies and raise incomes, complicating efforts to reduce it (Felbab‐Brown, 2017). Furthermore, emerging trends in IWT illustrate how even among issues that attract much attention (e.g., the illegal trade in tiger Panthera tigris parts and derivatives) (Esmail et al, 2020), changing poaching methods, new actors, and new trade routes and destinations require knowledge gaps to be filled to understand the patterns of supply, trade, and demand—which is complicated by the covert nature of the trade (Davis et al, 2020; Khanwilkar et al, 2022; Linkie et al, 2018; Musing, 2020; Nijman et al, 2019; Skidmore, 2021; Wong, 2019a, 2019b).…”
Section: Introductionmentioning
confidence: 99%